Optimization and Kinetic Studies on Biodiesel Conversion from Chlorella vulgaris Microalgae Using Pyrrolidinium-Based Ionic Liquids as a Catalyst - Hasanudin, N. (MDPI, 2022)
This study describes the potential conversion of dried microalgae. Chlorella vulgaris (C. vul-garis) into fatty acid methyl ester (FAME) using the direct transesterification (DT) method and using ionic liquids (ILs) as a catalyst. In this work, the performance of monocationic IL, namely 1-butyl-1-methylpyrrolidinium bromide (IL 1), and dicationic IL, namely 1,4-bis(1-methylpyrrolidinium-1-yl) butane dibromide (IL 2), as catalysts was compared for DT of C. vulgaris under microwave irradiation. The results revealed that IL 2 showed a better performance in catalyzing the DT reaction by producing 87.9 mg/g of FAME, while the use of IL 1 led to 74.3 mg/g of FAME under optimum conditions. The kinetic study for direct transesterification of C. vulgaris showed that the reaction followed a first order kinetic reaction where the activation energies were calculated to be 22.2499 kJ molâ1 and 22.0413 kJ molâ1 for IL 1 and IL 2, respectively. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.